2018
DOI: 10.1017/s1355617718000413
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal Changes in Resting State Connectivity and White Matter Integrity in Adolescents With Sports-Related Concussion

Abstract: Acute effects of SRC are associated with both hyperconnectivity and hypoconnectivity, with disruption of white matter integrity. In addition, acute memory performance was most sensitive to these changes. After 21 days, adolescents with SRC returned to baseline performance, although chronic hyperconnectivity of these regions could place these adolescents at greater risk for secondary neuropathological changes, necessitating future follow-up. (JINS, 2018, 24, 781-792).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 54 publications
0
47
2
Order By: Relevance
“…We propose that widespread injury can reduce rule-based skilled performance through a failure to communicate between brain networks. Cognitive brain network alterations have been observed following concussion (13)(14)(15)(16)(17). To assess the communication between brain areas for movement control, our group developed a touch screen based functional assessment tool using a visuomotor task that incorporates two forms of non-standard mapping: explicit rule integration (strategic control), and implicit spatial vision-to-hand-motion realignment (sensorimotor recalibration).…”
Section: A Failure To Communicate: the Effect Of Mild Brain Injury Onmentioning
confidence: 99%
“…We propose that widespread injury can reduce rule-based skilled performance through a failure to communicate between brain networks. Cognitive brain network alterations have been observed following concussion (13)(14)(15)(16)(17). To assess the communication between brain areas for movement control, our group developed a touch screen based functional assessment tool using a visuomotor task that incorporates two forms of non-standard mapping: explicit rule integration (strategic control), and implicit spatial vision-to-hand-motion realignment (sensorimotor recalibration).…”
Section: A Failure To Communicate: the Effect Of Mild Brain Injury Onmentioning
confidence: 99%
“…Several resting state fMRI studies of concussed athletes showed reduced functional connectivity in several neural networks in the acute and chronic periods following mTBI [93,96]. Murdaugh et al interestingly found resting state fMRI hyper connectivity in posterior brain regions (left cerebellum and precuneus, and right middle occipital gyrus, p = 0.047, <0.0001, 0.001, respectively) and hypoconnectivity in anterior brain regions (right inferior frontal gyrus (IFG), middle frontal gyrus (MFG), middle temporal gyrus (MTG), and posterior cingulate, p = 0.005, 0.05, 0.013, 0.01, respectively) in high school football players with SRC compared to those without [97]. More recent reviews of resting state fMRI in SRC have shown that changes in functional connectivity have the potential to predict SRC recovery profiles and clinical outcomes.…”
Section: Future Directionsmentioning
confidence: 99%
“…Numerous groups have sought to leverage neuroimaging data to not only detect mTBIs reliably and objectively, but also track brain recovery. At the group-level, structural changes in the integrity of white matter in adolescents has been observed using diffusion tensor imaging (DTI) [20,[27][28][29][30][31][32]. Similarly, studies of youths during "resting state" reveal significant mTBI-induced alterations in the functional organization of the brain with respect to their healthy counterparts, with key features being (i) a shift in spectral profile toward higher frequencies in the frontal brain regions, [33] (ii) an increase in functional connectivity (hyperconnectivity) [17,34,35], and (iii) disrupted information flow patterns [24], again particularly in the frontal regions.…”
Section: Introductionmentioning
confidence: 99%